2014
DOI: 10.1140/epjc/s10052-014-3025-x
|View full text |Cite
|
Sign up to set email alerts
|

Self-dual chiral boson: augmented superfield approach

Abstract: We exploit the standard tools and techniques of the augmented version of the Bonora-Tonin superfield formalism to derive the off-shell nilpotent and absolutely anticommuting (anti-)Becchi-Rouet-Stora-Tyutin (BRST) and (anti-)co-BRST symmetry transformations for the BRSTinvariant Lagrangian density of a self-dual bosonic system. In the derivation of the full set of the above symmetry transformations, we invoke the (dual-)horizontality conditions, and (anti-)BRST-and (anti-)co-BRST-invariant restrictions on the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(52 citation statements)
references
References 30 publications
0
52
0
Order By: Relevance
“…In Ref [10], we find an interesting description towards quantization of that free FJ type chiral boson. In a very resent work [11], we find an application of augmented super field approach to derive the off-shell nilpotent and absolutely anti-commuting (anti-)BRST and (anti-)co-BRST symmetry transformations for the BRST invariant Lagrangian density of a free chiral boson. Another recent important development towards the BFV quantization of the free chiral boson along with study of Hodge decomposition theorem in the context of conserved charges has came in [12] The obvious generalization of free chiral boson is to take into account of the interaction of gauge field with that and this interacting field theoretical model is known as gauged model of chiral boson.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref [10], we find an interesting description towards quantization of that free FJ type chiral boson. In a very resent work [11], we find an application of augmented super field approach to derive the off-shell nilpotent and absolutely anti-commuting (anti-)BRST and (anti-)co-BRST symmetry transformations for the BRST invariant Lagrangian density of a free chiral boson. Another recent important development towards the BFV quantization of the free chiral boson along with study of Hodge decomposition theorem in the context of conserved charges has came in [12] The obvious generalization of free chiral boson is to take into account of the interaction of gauge field with that and this interacting field theoretical model is known as gauged model of chiral boson.…”
Section: Introductionmentioning
confidence: 99%
“…Further, we have found that the geometrical interpretation for the symmetry transformations remains intact in our present method of derivation vis-à-vis the ones where the mathematical strength of the (dual-)horizontality conditions is properly utilized [37]. Thus, both methods of derivation are consistent and, in some cases, complementary to each other (see, e.g., [20,21,33,34]).…”
Section: Discussionmentioning
confidence: 73%
“…The invariance of gauge-fixing term under the (anti-)co-BRST transformations can be captured in the following (anti-)co-BRST invariant restriction [17,28] ⋆d ⋆Z (1)…”
Section: Off-shell Nilpotent (Anti-)brst Symmetries: Supervariable Apmentioning
confidence: 99%
“…For the interacting theories, a more powerful method known as "augmented" version of the superfield approach has been developed where, in addition to the horizontality condition, the gauge-invariant restrictions are also implemented for the derivation of the complete set of proper (anti-)BRST transformations [27][28][29][30]. In our present study, we shall utilize the power and strength of the superfield formalism to derive the off-shell nilpotent and absolutely anticommuting (anti-)BRST as well as (anti-)co-BRST symmetry transformations for the (0+1)-dimensional CL model.…”
Section: Introductionmentioning
confidence: 99%